Axial Compression Test and Bearing Capacity Analysis of Biaxial Prestressed Angle Steel Plate Fully Wrapped Reinforced Concrete Short Column. (9th April 2022) - Ren, Zhenhua; Zeng, Xiantao; Shen, Yaqian; Huang, Huanlin
Abstract : A new external reinforcement method is proposed in this research by using the prestressed angle steel plate to fully wrap a reinforced concrete column with a rectangular cross section. To study the axial compression characteristics of the new proposed structure, twenty pieces of the concrete columns were built using the normal reinforcement: five control columns and fifteen reinforced concrete columns, with three groups of different prestressed angle steel plates. These columns were tested under axial compression after the completion of the reinforcement. The experimental results showed that the ultimate load-bearing capacities of the three groups of the reinforced concrete columns with different prestress levels were increased by 35.6%, 52.7%, and 61.7% compared with the control columns. Both the ultimate strain and the deformation were improved significantly. The load-bearing capacity equation of the reinforced column was deduced based on the unified strength theory, and the accuracy of the equation was validated. Moreover, a finite element simulation was performed for the new structure, and the simulation results were in good agreement with the test results. Simulation results are in good agreement with the experimental results.